2008
DOI: 10.1111/j.1540-8183.2008.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Verification of a Theory for Predicting Side Branch Stenosis after Main Vessel Stenting in Coronary Bifurcation Lesions

Abstract: Our analysis shows that the most powerful independent predictor of SB compromise is a new variable angle alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…Stent implantation over a bifurcation lesion with or without subsequent post-dilation might induce geometrical changes of the SB ostium leading to observations of angiographic SB compromise during the procedure. These geometrical changes appear to be the combination of two effects: (i) the straightening of the MB that stretches the SB, and (ii) the displacement of the carina towards the SB because of stent expansion [7][8][9][10]27 , confirming observations of other numerical studies on single patients 26,28 . Although angiographic images might demonstrate a significant lumen compromise, this is rarely accompanied by a haemodynamically significant compromise, as demonstrated by post-implantation FFR measurements of the SB 7 .…”
Section: Discussionsupporting
confidence: 77%
“…Stent implantation over a bifurcation lesion with or without subsequent post-dilation might induce geometrical changes of the SB ostium leading to observations of angiographic SB compromise during the procedure. These geometrical changes appear to be the combination of two effects: (i) the straightening of the MB that stretches the SB, and (ii) the displacement of the carina towards the SB because of stent expansion [7][8][9][10]27 , confirming observations of other numerical studies on single patients 26,28 . Although angiographic images might demonstrate a significant lumen compromise, this is rarely accompanied by a haemodynamically significant compromise, as demonstrated by post-implantation FFR measurements of the SB 7 .…”
Section: Discussionsupporting
confidence: 77%
“…Recently, Vassilev et al showed that the most powerful independent predictor for SB compromise is angle α, which is the angle between the main vessel axis before SB and the internal side of the SB wall, extending up to the flow divider [21]. This angle corresponds to 180-MV angle in our data.…”
Section: Discussionmentioning
confidence: 54%
“…4 However, some angiographic studies have demonstrated that a stent-induced increase in lumen diameter of the MVd shifted the carina into the SBo, and this carina shift was the main mechanism of SB ostial narrowing after MV stent implantation. 8,9 A recent IVUS study indicated that the vessel and lumen volumes increased in both the MVp and MVd, whereas only the plaque volume of the MVp decreased and the plaque volume of the MVd remained unchanged after MV stenting. 10 The authors speculated that the degree of luminal narrowing of an SB after stenting of the MV was a result of carina shift.…”
Section: Mechanism Of Aggravation Of Sb Ostial Stenosismentioning
confidence: 99%
“…Vassilev et al 8 reported that carina angle was the most powerful independent predictor of SBo compromise in their quantitative coronary angiography analysis. 8 And Kang et al 11 also found that narrow carina angle between the left anterior descending and the left circumflex coronary artery and wide angle between the left circumflex coronary artery and the left main lesions were associated with a greater lumen area loss at the left circumflex coronary artery ostium. 11 But in our study, we could not find any correlation between bifurcation angle or carina angle and SBo compromise, carina shift, or plaque shift.…”
Section: Bifurcation Angle and Sbo Compromisementioning
confidence: 99%
See 1 more Smart Citation